2016
DOI: 10.4103/2229-5151.195449
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between pulmonary artery pressures and inferior vena cava collapsibility in critically ill surgical patients: An exploratory study

Abstract: Introduction:As pulmonary artery catheter (PAC) use declines, search continues for reliable and readily accessible minimally invasive hemodynamic monitoring alternatives. Although the correlation between inferior vena cava collapsibility index (IVC-CI) and central venous pressures (CVP) has been described previously, little information exists regarding the relationship between IVC-CI and pulmonary artery pressures (PAPs). The goal of this study is to bridge this important knowledge gap. We hypothesized that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…The CVC changes diameter during the respiratory cycle . With inspiration, the CVC diameter in the cranial abdomen decreases and with expiration it increases.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The CVC changes diameter during the respiratory cycle . With inspiration, the CVC diameter in the cranial abdomen decreases and with expiration it increases.…”
mentioning
confidence: 98%
“…Recent studies have identified numerous deficiencies with the current methods used to estimate fluid status, including heart rate, blood pressure, physical examination findings, and laboratory findings . A rapid and noninvasive method recently investigated to assess fluid status in humans involves the use of sonography to measure the change in diameter of the caudal vena cava (CVC) with inspiration and expiration …”
mentioning
confidence: 99%
“…In intensive care patients, IVCI correlates well with invasively measured central venous pressure and pulmonary artery pressure (Stawicki et al . ; Ilyas et al . ).…”
Section: Cardiorenal Syndromesmentioning
confidence: 99%
“…Another way to estimate an individual's intravascular filling state non-invasively is the ultrasound derived inferior vena cava collapsibility index (IVCI) (Finnerty et al 2017). In intensive care patients, IVCI correlates well with invasively measured central venous pressure and pulmonary artery pressure (Stawicki et al 2016;Ilyas et al 2017). In comparison to uncomplicated pregnancies, reduced IVCI was observed in late-onset but not in early-onset preeclampsia, suggesting a higher intravascular filling state in late-onset than in early-onset preeclampsia (Stergiotou et al 2013).…”
Section: Direct Cardiorenal Interactionsmentioning
confidence: 99%
“…IVCI is defined as (IVmax − IVmin)/IVmax, where IVmax is the IVC diameter at maximal inspiration and IVmin at maximal expiration. In patients at intensive care units (ICU), IVCI correlates well with invasively measured central venous pressure and pulmonary artery pressure [38,39]. In comparison to uncomplicated pregnancies, reduced IVCI was observed in LPE but not in EPE, suggesting a higher intravascular filling state in LPE than in EPE [40].…”
Section: Renal Physiology In Normal Pregnancy and In Two Types Ofmentioning
confidence: 99%